PROBLEMS OF CONTROLLING THE COSTS OF OPERATING ACTIVITIES OF CONSTRUCTION BUSINESS STRUCTURES IN THE CONTEXT OF STRENGTHENING INTERNATIONAL COOPERATION - Леся Гнилянська; Юрій Шпак; Віта Довга (Економіка та суспільство)
This article discusses the issue of controlling the costs of operating activities of business structures. Attention is focused on enterprises in the construction industry in the context of strengthening international cooperation between Ukraine and Japan. The main areas of international cooperation include: infrastructure projects and reconstruction, financial assistance and investments, joint business platforms and forums, technological cooperation and innovations. The article analyzes practical approaches to the implementation of international cooperation in the construction sector, highlights the features of controlling the costs of operating activities of construction enterprises. The international experience, in particular of Japan, in the development of priority areas of cooperation in the construction sector has been studied. The structure of costs for the operating activities of construction enterprises is systematized. Priority areas for the development of cooperation in the field of construction are presented. Recommendations are given on solving the problems of controlling the operational activities of construction enterprises in the context of strengthening international cooperation.